الضيافة وأثرها في تنمية المجتمع في ضوء السنة النبوية: دراسة تحليلية - محمد، أحمد حسن (Kulliyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2017)
This study uses inductive and analytical methods, and addresses the subject of hospitality and its impact on community development in light of the Prophetic Tradition (al-sunnah al-nabawiyyah). The study elucidates the concept of hospitality, its religious status and related terms, and also illustrates types and manners of hospitality as well as the meaning of guest and the host in the Prophetic Tradition. The study explains the meaning of development, the society and related terms. It also explains the basic elements of social development in the Prophetic Tradition, with special emphasis on the need to preserve the inborn character of man and woman, the foundations of good moral conduct and the essential role of family life. However, the study demonstrates the impact of hospitality on the social development in the Prophetic Tradition (al-sunnah al-nabawiyyah), with particular focus on the connection between hospitality and human rights, the impact of good hospitality on spiritual development, and a concise account on the negative implications of undesirable treatment of guests on the society. The study highlights the importance of hospitality and its impact on the social solidarity (al-takaful al-ijtima'i). The research also addresses the meaning and elements of social solidarity according to the Prophetic Tradition, and the connection between hospitality and Islamic endowments (al-awqaf), the sacrificial animals (al-adahi) and weddings (al-'urs). The study offers a brief overview on the impact of hospitality on education and the expansion of knowledge as well as on social awareness. The study concludes that: among the type of hospitality mentioned in the Prophetic sunnah is continues hospitality, hospitality of visitors, hospitality of guests, hospitality of armies and hospitality of wedding invitees. It also concludes among the basic elements of social development that Sunnah promotes is preservation of the inborn character (hifz al-fitrah), good moral conducts (al-akhlaq al-karimah) and matrimonial life. Good hospitality also has a significant impact on the spiritual enhancement and protection of the human rights, as well as on elements that are set to upgrade social solidarity such as endowments, sacrificial animals, wedding ceremonies and education and expansion of knowledge.